1957
DOI: 10.1002/jcp.1030500206
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the polysaccharides of aquatic snails

Abstract: This pa1)er presents a more detailed study of the sugars occui,i+ig in the polysaccliai*ides of aquatic snails, with particular c1iiipliasis 011 tliosc of tlic reproductive tract and eggs. RIATERIAI, A M ) MIETlIODSS l Z n il s T\'hole snails and isolated organs were employed as follows :1. Australorbis gltrbrntus, Venezuelan strain, laboratoryreared. TThole adult snails, isolated albumen glands, and egg clutclies of various ages ~v c r c uscd.2. Lpiizncrecc s t n g w l i s , laboratory-reared from \\'isconsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1961
1961
1990
1990

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…3 a) . A more extensive autoradiographic analysis has been reported by Fucose is incorporated into a variety of polysaccharides (27) and is known to be a component of mucous secretions in Aplysia and several other marine animals (28) . Pronase digestion of labeled macromolecules from R2, however, indicated that fucose was predominantly, if not entirely, incorporated into glycoproteins : less than 25% of the digest remained large enough to be excluded AMBRON ET AL .…”
Section: Identification Of [°H]fucose In Hydrolysates Ofmentioning
confidence: 99%
“…3 a) . A more extensive autoradiographic analysis has been reported by Fucose is incorporated into a variety of polysaccharides (27) and is known to be a component of mucous secretions in Aplysia and several other marine animals (28) . Pronase digestion of labeled macromolecules from R2, however, indicated that fucose was predominantly, if not entirely, incorporated into glycoproteins : less than 25% of the digest remained large enough to be excluded AMBRON ET AL .…”
Section: Identification Of [°H]fucose In Hydrolysates Ofmentioning
confidence: 99%
“…The formation and composition of thc egg capsule in numerous pulmonates (Lymnaea stagnalis, McMahon et al, 1957; Succineu putris, George and Jura, 1958; Ariophata ligulara, Rangarao, 1963; A g r i o l i m reticulurw, Bayne, 1966Bayne, , 1967; Biomphalaria glabrara, Jong-Brink, 1969; Bulinus fruncatus, Jong-Brink et al, 1979) has bcen studicd. The fluid components from the albumen gland include galactogen (McMahon el al., 1957;Rangarao, 1963;Bayne, 1967;Jong-Brink et al, 1979), mucopolysaccharides from the sperm-oviduct (Rangarao, 1963) or muciparous gland (Jong-Brink, 1969;Jong-Brink et al, 1979) and protein with plysaccharides and glycogcn (George and Jura, 1958;Bayne, 1966).…”
Section: Discussionmentioning
confidence: 98%
“…The H-like components from P. pa ludosa eggs, L. littorea, T. rivulorum and L. terrestris are being isolated and it will be interesting to examine and compare the constituent sugars in each of these preparations with the sugars present in the various snail galactogens. The galactogen from L. stagnalis has already been studied and is known to differ from H. pomatia galactogen in that it contains L-fucose instead of L-galactose [26]. The isolation of the various H-like components will also permit quantitative studies to be carried out and thus help in the identifica tion of the structures involved in the reactions with the different anti-H reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Water snail (Lymnaea stagnalis) galactogen was prepared according to methods already described [20,26],…”
Section: Galactogensmentioning
confidence: 99%